Risk Management in Circular Economy Projects: Engineering Management Challenges and Solutions in Nigeria - Hyginus Unegbu; Danjuma S. Yawas (Journal of Sustainable Infrastructure, 2026)
Circular economy (CE) implementation offers promising pathways for sustainable development, resource efficiency, and waste minimization. However, the transition from linear to circular systems presents considerable engineering management challenges, especially in developing economies such as Nigeria, where socio-institutional complexity, regulatory uncertainty, and infrastructural limitations persist. This study critically examines the risk landscape associated with engineering-managed CE projects in Nigeria, with the objective of identifying, quantifying, and prioritizing key risk factors that undermine project delivery and long-term sustainability. A sequential exploratory mixed-methods design was adopted, combining qualitative insights from expert interviews with advanced quantitative modeling. Risk data were analyzed using Monte Carlo simulation to estimate probabilistic impact, Principal Component Analysis (PCA) to uncover latent risk structures, and Fuzzy Analytic Hierarchy Process (FAHP) to prioritize mitigation strategies under uncertainty. Five major risk dimensions were evaluated: technical failure, regulatory delay, stakeholder conflict, financial overrun, and supply chain disruption. Findings revealed that stakeholder conflict and regulatory delay are the most severe and probable risks, accounting for the highest variance in risk exposure. Technical risks, while relevant, were found to be less critical in shaping project success than governance-related variables. The analysis underscores the need for a shift in engineering risk management from traditional design-centric models to integrative frameworks that incorporate policy, finance, and stakeholder dynamics. This research offers a replicable methodological approach for CE project risk analysis in developing countries. It also provides evidence-based guidance for engineering managers, policymakers, and investors seeking to enhance the resilience and performance of CE infrastructure.